The Impact of Health Informatics and Medical Secretarial Support on Dental Care Quality and Administrative Efficiency - Dr. Osama Abdullah Alqarni; Dr. Amr Ahmed Alghamdi; Dr. Hussam Hatim Abualola; Amal Abdulkarim Al Rubeh; Abdulkarim Mohsen Ayedh Albagami; Adel Saleh Awadh Algethami; Saif Hussain Saeed Alharthi; Fahad Saed Alharthi; Ghazi Abdulhadi Matar Alrobaie; Rayd Khadir Eabdallah Alruwqi; Fatima Mansoor Almarzooq; Samiha Abdulkarim Al Rubh (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Health informatics and medical secretarial support are crucial for the efficient provision of excellent dental healthcare and the proper administration of services. Electronic Health Records, telemedicine, and data analytics enhance clinical decision-making, work coordination, and patient outcomes. Telehealth services save travel and wait times in remote areas, while medical secretarial support manages appointment scheduling, fees, and activity coding. Nurse-prescribed and developed treatments reduce burnout among ward clinicians, improve patient outcomes, and increase practice efficiency. It is pretty likely that advancements in technology will lead to further growth in health informatics used in dental treatment, improving both the quality of care and accessibility. Aim of work: To investigate the impact of health informatics and medical secretarial support on dental care quality and administrative efficiency Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Impact, Health Informatics, Medical Secretarial, Support, Dental Care, Quality and Administrative Efficiency.The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion:Medical Secretaries and Health Informatics are essential for improving the dental care process and direct or indirect organizational/administrative processes. New technology innovations, including EHRs, data analytics and telemedicine are making dental treatment more common. Medical and clinical secretarial services take care of the administrative tasks, enabling the dental professionals to focus on their clinical work! However, there will be improvement of health informatics integration and more training on medical secretaries which benefits in both ways. Further studies should focus on advancing/making Health Informatics sophisticated tools and medical secretary training programs.